Kovaa työtä olla minä : muotibloggaajat mediamarkkinoilla - Noppari, Elina; Hautakangas, Mikko (Tampere University Press, 2012)
English summary.
Keywords: viestintä; blogit; muoti; markkinointi; sosiaalinen media; mediakulttuuri; Internet; vuorovaikutus; pukeutuminen; verkkojulkaisut; päiväkirjat; tyylit; trendit; yleisö; muotiala; kommunikation; bloggar; mode; marknadsföring; sociala medier; mediekultur; internet; växelverkan; klädsel; webbpublikationer; dagböcker; stilar; trender; publik; modebranschen